Sexual Compulsivity among Indonesian College Students. (29th March 2019) - Nugroho, Rico Maulana; Afiyanti, Yati
ABSTRACT: The objective of this study is to describe the sexual compulsivity of Indonesian college students. We used a cross-sectional design and recruited 301 college students in Universitas Indonesia. Data were collected using the modified Sexual Compulsivity Scale (SCS) instrument. These findings show that Indonesian students have lower sexual compulsivity scale (mean: 11.39 ± 4.21). Male students have significantly higher SCS score than female students ( p = 0.000). Working students were also found to have a higher SCS score than those who did not work ( p = 0.039). Further studies on sexual compulsivity among young adults in Indonesia are deemed necessary to give more understanding about sexual compulsivity. These findings provide basic information to design a sexual counseling method for improving the sexual health of young adults.